KONTROL OPTIMAL PADA MODEL PENYEBARAN VIRUS KOMPUTER DENGAN KLASIFIKASI PENGAMANAN - DARAJAT, PANGESTUTI PRIMA; HUSADANINGSIH, TYAS (E-Jurnal Matematika; Vol 8 No 4 (2019), 2019)
In this paper, a model of the spread of computer viruses  with security classification and nonlinear infection rates is formulated. From the short analysis, is found that the model does not have a virus-free equilibrium point. This show that the virus will always exist in the system and increasingly that can not be avoided. Therefore, control strategy by installing antivirus on subpopulation susceptible low-security level and infective subpopulation aims to minimize the number of infective computers, and  minimize the cost related to these strategies. Hence, an important tool, in this case is, optimal control theory. The system solved numerically by using Forward-Backward Sweep method in combination with the fourth-order Runge-Kutta method. Based on the simulation results, the combination of the two controls is effective in suppressing the spread of computer viruses. However, controlling by installing an antivirus on an infected computer has a great influence in suppressing the spread of the computer virus.